Augmenting family based treatment with emotion coaching for adolescents with anorexia nervosa and atypical anorexia nervosa: Trial design and methodological report - Claire M. Aarnio-Peterson; Constance A. Mara; Avani C. Modi; Abigail Matthews; Daniel Le Grange; Anne Shaffer (Contemporary Clinical Trials Communications, 2023)
This article characterizes the design, recruitment, methodology, participant characteristics, and preliminary feasibility and acceptability of the Families Ending Eating Disorders (FEED) open pilot study. FEED augments family-based treatment (FBT) for adolescents with anorexia nervosa (AN) and atypical anorexia nervosa (AAN) with an emotion coaching (EC) group for parents (i.e., FBT + EC). We targeted families high in critical comments and low warmth (assessed by the Five-Minute Speech Sample), known predictors of poor response in FBT. Eligible participants included adolescents initiating outpatient FBT, diagnosed with AN/AAN, ages 12–17, with a parent high in critical comments/low in warmth. The first phase of the study was an open pilot which demonstrated feasibility and acceptability of FBT + EC. Thus, we proceeded with the small randomized controlled trial (RCT). Eligible families were randomized to either 10 weeks of FBT + EC parent group treatment or the 10- week parent support group (control condition). The primary outcomes were parent critical comments and parental warmth, while our exploratory outcome was adolescent weight restoration. Novel aspects of the trial design (e.g., specifically targeting typical treatment non-responders), as well as recruitment and retention challenges in the context of the COVID-19 pandemic are discussed.